Exploratory study of autophagy inducer sirolimus for childhood cerebral adrenoleukodystrophy - Luo, Xiao-Mei; Liu, Li-Ying; Wang, Qiu-Hong; Wang, Yang-Yang; Wang, Jing; Yang, Xiao-Yan; Li, Shi-Jun; Zou, Li-Ping (Frontiers in Pediatrics, 2023)
Objectives: X-linked adrenoleukodystrophy (ALD) is a peroxisomal disease caused by mutations in the ABCD1 gene. Childhood cerebral ALD (CCALD) is characterized by inflammatory demyelination, rapidly progressing, often fatal. Hematopoietic stem cell transplant only delays disease progression in patients with early-stage cerebral ALD. Based on emergency humanitarianism, this study aims to investigate the safety and efficacy of sirolimus in the treatment of patients with CCALD. Methods: This was a prospective, single-center, one-arm clinical trial. We enrolled patients with CCALD, and all enrolled patients received sirolimus treatment for three months. Adverse events were monitored and recorded to evaluate the safety. The efficacy was evaluated using the neurologic function scale (NFS), Loes score, and white matter hyperintensities. Results: A total of 12 patients were included and all presented with CCALD. Four patients dropped out and a total of eight patients in the advanced stage completed a 3-month follow-up. There were no serious adverse events, and the common adverse events were hypertonia and oral ulcers. After sirolimus treatment, three of the four patients with an initial NFS>10 showed improvements in their clinical symptoms. Loes scores decreased by 0.5 to 1 point in two of eight patients and remained unchanged in one patient. Analysis of white matter hyperintensities revealed a significant decrease in signal intensity (n=7, p = 0.0156). Conclusions: Our study suggested that autophagy inducer sirolimus is safe for CCALD. Sirolimus did not improve clinical symptoms of patients with advanced CCALD significantly. Further study with larger sample size and longer follow-up is needed to confirm the drug efficacy.